Effect of Adding Various Qualities of Litter and Urea on the Growth of Earthworms (Pontoscolex corethrurus) and Soil Microorganism Populations - Retno Widiyanti (Contributions of Central Research Institute for Agriculture, 2021)
This study aims to determine the effect of adding a mixture of coffee litter + Gliricid + durian and Urea and its combination on the growth of Pontoscolex streak worms and the population of soil microorganisms, especially bacteria and fungi, and whether worm growth can increase the population of bacteria and fungi. The results of this study indicated that the addition of litter (coffee+Gliricidia+durian) ja increased worm biomass by 29% compared to the addition of Urea (0.28g/head) and increased the diameter of the worms by 12% compared to the addition of Urea(0.25mm/head) . The combination of litter and Urea increased the bacterial population by 16% compared to the addition of Urea alone (32.105cfu/ml), while compared to the addition of only litter (34.105cfu/ml) the bacterial population increased by around 9%.